2020
DOI: 10.11114/aef.v7i2.4710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Economic Growth, Trade Openness, and Urbanization on Carbon Dioxide Emissions in Ghana, 1960 to 2014

Abstract: This paper examines the effects of per capita gross domestic product (GDP), trade openness, and urbanization on the total carbon dioxide emissions of Ghana using time-series annual data from 1960 to 2014. The 55-year period, from 1960 to 2014, covered economic transformation of Ghana from a low-income agrarian country to a lower-middle income country. The analysis used the autoregressive distributed lag method of co-integration. The results showed that per capita GDP, trade openness, and urbanization all signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Mineral mining is just one example of an activity that has a direct human impact on the local ecosystem and can have severe consequences (Soylu et al, 2021). One of the most pressing issues confronting modern-day South Africa is climate change, which has its roots in the unsustainable use of nonrenewable and leads to higher emissions and other forms of greenhouse gas pollution (Boateng, 2020). According to Soylu et al (2021), carbon emissions are one of the Greenhouse Gases (GHGs) widely understood to be the primary factor in climate change and environmental degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Mineral mining is just one example of an activity that has a direct human impact on the local ecosystem and can have severe consequences (Soylu et al, 2021). One of the most pressing issues confronting modern-day South Africa is climate change, which has its roots in the unsustainable use of nonrenewable and leads to higher emissions and other forms of greenhouse gas pollution (Boateng, 2020). According to Soylu et al (2021), carbon emissions are one of the Greenhouse Gases (GHGs) widely understood to be the primary factor in climate change and environmental degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The study confirmed that trade openness contributes to carbon emissions. On the contrary, Kwakwa & Alhassan (2018), Kwakwa et al (2019) and Boateng (2020) found that trade improves the environment by contributing to emission reduction in Ghana.…”
Section: Related Literaturementioning
confidence: 97%
“…e dynamic relationship between logistics performance, environmental degradation, and energy in Asian countries has been studied in this paper based on the experience of existing literatures. Besides LPI, a large number of researches also show that trade openness, urbanization, and industrialization have effects on environment and energy consumption [54][55][56]. First of all, international trade is the prerequisite for the survival of international logistics, and it is also the basis for solving the obstacles of transnational supply chain, so global procurement and international trade must be considered in logistics operation [57].…”
Section: Empirical Modelmentioning
confidence: 99%